Evaluate the optimal stent duration following endourology procedures: 5 days versus 14 days - Banerjee, Avijit; P., Velmurugan; K. , Natarajan (International Surgery Journal, 2023)
Background: Most urologists prefer not to place a stent in an uncomplicated URS (ureterorenoscopy) in the post-op period. Even if they do so, they place it with an extraction string that can be removed in post-op day 3-5 based on the patient’s compliance. Here we sought to determine the optimal duration of stenting following endo-urology procedures (URSL, RIRS, PCNL) for stone disease (5 days vs 14 days). Methods: It was a prospective randomised study where 1547 patients were evaluated over a span of 1.5 years, 671 of whom stent was removed on day 5 and 876 of whom stent was removed on day 14. Results: Of all the patients, 32% experienced post-procedure-related events within 30 days (15% of 5-day stent removal compared to 44.9% of 14-day patients). Conclusions: Removal of the stent on the 5th day does not warrant re-procedure and is associated with fewer post-procedure-related symptoms.